PENEGAKAN HUKUM OLEH POLISI RESOR KOTA PEKANBARU TERHADAP PEREDARAN MINUMAN KERAS IMPOR ILEGAL OLEH PEDAGANG GEROBAK DORONG DI JALAN JUANDA KOTA PEKANBARU - Anrifa, Rianty; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
As which it is known that the circulation of liqour despite tighneted in terms of administration, it was not able to stem it’s spread. Many trader do cheating antecedent to avoid the complexity of the administrative permit one of which is the sale of illegally imported liquor.In law enforcement against traders who sell liquor are expected officers to be able to crack down firmly. Community participation is also expected to oversee, for goverment enforcement and implementation of regulations should be strengthened and not going nowhere.Keyword : Circulation – liquor – trader